2006
DOI: 10.1161/01.atv.0000202662.63876.02
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Lipase Deficiency Delays Atherosclerosis, Myocardial Infarction, and Cardiac Dysfunction and Extends Lifespan in SR-BI/Apolipoprotein E Double Knockout Mice

Abstract: Objective-SR-BI/apolipoprotein (apo) E double knockout (dKO) mice exhibit many features of human coronary heart disease (CHD), including occlusive coronary atherosclerosis, cardiac hypertrophy, myocardial infarctions, and premature death. Here we determined the effects on this pathology of hepatic lipase (HL) deficiency, which has been shown to significantly modulate atherosclerosis. Method and Results-The SR-BI/apoE/HL triple knockout (tKO) mice generated for this study lived significantly longer (37%) than c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…However, the double apo E/SR-BI KO mice have increased cholesterol (serum cholesterol levels 800 to 1000 mg/dl) and accelerated atherosclerosis ( 4 weeks of age) [119]. Yu et al [120] found that macrophage apo E promotes reductions in serum cholesterol levels, improves HDL subpopulations, provides extensive protection from atherosclerotic lesion development, and prevents premature death in double apo E/SR-BI KO mice [120,121]. Furthermore, treatment of SR-BI/apo E KO mice with probucol (a lipid lowering drug) extended their lives (from 6 to 36 weeks) and essentially reversed all early-onset CHD-associated anatomical, functional, cellular and biochemical pathology [118].…”
Section: Scavenger Receptor Class B Type I (Sr-bi)mentioning
confidence: 99%
“…However, the double apo E/SR-BI KO mice have increased cholesterol (serum cholesterol levels 800 to 1000 mg/dl) and accelerated atherosclerosis ( 4 weeks of age) [119]. Yu et al [120] found that macrophage apo E promotes reductions in serum cholesterol levels, improves HDL subpopulations, provides extensive protection from atherosclerotic lesion development, and prevents premature death in double apo E/SR-BI KO mice [120,121]. Furthermore, treatment of SR-BI/apo E KO mice with probucol (a lipid lowering drug) extended their lives (from 6 to 36 weeks) and essentially reversed all early-onset CHD-associated anatomical, functional, cellular and biochemical pathology [118].…”
Section: Scavenger Receptor Class B Type I (Sr-bi)mentioning
confidence: 99%
“…Studies show that (a) HL is a liver-secreted enzyme that hydrolyzes triglycerides and phospholipids and is involved in processing large lipid-rich HDL into smaller HDL particles (18), and (b) the ligand-binding activity of HL may mediate interactions of lipoproteins with SR-BI or the plasma membrane, thus facilitating selective HDL-CE uptake (19)(20)(21)(22)(23)(24). As such, mice lacking expression of either SR-BI or HL have elevated levels of HDL-C and impaired HDL-C clearance by hepatocytes (14,(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of SR-BI on murine atherosclerosis has been examined in both the LDL receptor and apoE knockout models. Hepatic overexpression of SR-BI suppresses and loss of SR-BI expression enhances atherosclerosis in these models (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The atheroprotective activity of SR-BI, even though its expression decreases plasma HDLcholesterol levels, suggests that SR-BI's role in reverse cholesterol transport (the movement of cholesterol from peripheral tissues to the liver and then excretion in the bile) may contribute to its protective activity in mice.…”
mentioning
confidence: 99%